Development of integrated processes for the coproduction of inulin, protein, and ethanol from Jerusalem artichoke tubers in a biorefinery - Maumela, Pfariso (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.